Transformasi Budaya Perusahaan Kelompok Kompas Gramedia - Ludwig Suparmo (Inter Komunika, 2016)
Within a few decades the leading national daily Kompas, grew in becoming the number one daily in Indonesia. Aside keeping-up with the press advancement, modernizing through its information technology printing and its long distance production has helped its production. The daily-paper then forming several publishing companies, and extending of other media went on, while the bookstores also grew well. However, it then extended into the non core business lines, such as producing and marketing tissue paper and participating in the growing sector of the hotel business. Jakob Oetama, one of the founders was made aware that he would be losing the span of control and at the same time was still much interested in setting a stronger corporate culture based on the company’s ideals which among others are to enlighten the social life and participating in influencing on practicing good governing system. Jakob Oetama who takes the lead always trusted his young dynamic managers, several years ago then, appointed Agung Adiprasetyo as the CEO. The team then formulated the transformation of their corporate culture; not only by establishing a simple way to be easy followed by all the workers: Vision and Mission, that is stated together, but also adding the “5 Cs Values”: Caring, Credible, Competent, Competitive, Customer Delight.